2013
DOI: 10.1039/c3sm00125c
|View full text |Cite
|
Sign up to set email alerts
|

Hybrid gelation processes in enzymatically gelled gelatin: impact on nanostructure, macroscopic properties and cellular response

Abstract: Physical, chemical and hybrid tilapia fish gelatin hydrogels were investigated by small-angle neutron scattering (), molecular dynamic simulations and their biological effect in cell cultures studied; results from the different experimental techniques were then correlated and linked to the rheological properties of the gels (F. Bode et al., Biomacromolecules, 2011, 12, 3741-3752). Hydrogels were obtained by cross-linking with the microbial enzyme transglutaminase (mTGase) under two conditions: above and below … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
40
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 38 publications
(43 citation statements)
references
References 57 publications
2
40
1
Order By: Relevance
“…The first is a correlation length (ξ), which in the case of cross-linked hydrogels can be described as the length of the scattering center. 47,51 The second is the Lorentzian exponent, which carries information about the dimensionality of the scattering center. 53 …”
Section: Resultsmentioning
confidence: 99%
“…The first is a correlation length (ξ), which in the case of cross-linked hydrogels can be described as the length of the scattering center. 47,51 The second is the Lorentzian exponent, which carries information about the dimensionality of the scattering center. 53 …”
Section: Resultsmentioning
confidence: 99%
“…The gelatin solution in the Chirascan took approximately 2 min to reach the target temperature. The optical rotation angle calibration and correction has been described elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…They reported a higher storage modulus ( G ′) for chemical gels obtained in the presence of the physical network. Recently, we reported an extensive investigation on the enzymatically‐cross‐linked gels of tilapia fish gelatin . A combination of rheology, small‐angle neutron scattering and optical rotation revealed that the presence of the physical network drastically affects the rheological and microstructural properties of the gels.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, physical cross-linking by single strand to triple helix transition is homogeneously distributed throughout the mass. 10 For this reason, we first induced sol-gel transition and then covalently cross-linked gelatin filaments using EDC and NHS.…”
Section: Pattern Fabricationmentioning
confidence: 99%